Enhanced activity and stability of SO42â/ZrO2 by addition of Cu combined with CuZnOZrO2 for direct synthesis of dimethyl ether from CO2 hydrogenation - Witoon, T. (2022)
Cu-modified SO42â/ZrO2 catalysts (XCu-SZ) with different Cu loading contents were prepared by sulfation of ZrOCl2Â·8H2O with (NH4)2SO4 to form SO42â/ZrO2 (SZ) followed by impregnation of SZ with a Cu precursor. The resulting XCu-SZ catalysts combined with a CuOâZnOâZrO2 catalyst were tested for CO2 hydrogenation to dimethyl ether (DME). The results indicated that the unmodified SZ catalyst exhibited the maximum DME yield (3.7) which was 2.0â2.6 times higher than the DME yield of all XCu-SZ catalysts at the beginning of reaction. However, the DME yield over the unmodified SZ catalyst rapidly decreased, while that of all XCu-SZ catalysts gradually increased during the time-on-stream experiment. After 100 h, the 6 wt Cu-modified SZ catalyst achieved the maximum DME yield of 3.2 at 260 Â°C and 20 bar, while the DME yield of the unmodified SZ catalyst was only 2.5. The NH3-TPD and XPS analyses indicated that more strong acid sites were present on the unmodified SZ catalyst, resulting in a coke formation and thus the rapid deactivation. For the XCu-SZ catalysts, Cu0 was formed on the surface of SZ after the reduction with H2 which accounted for the active site of hydrogenolysis of methanol to methane. During the time-on-stream experiment, Cu0 was progressively transformed to Cu2S through poisoning, leading to the continued increase of DME yield. Â© 2022 Hydrogen Energy Publications LLC